Interventricular septal dissection secondary to acute inferior myocardial infarction: case series and literature review - Ping Chen; Xiuqin Wang; Yun Mou (Journal of Cardiothoracic Surgery)
Abstract Background Interventricular septal dissection is a critical disease characterized by the separation of the intraventricular septum into two layers, forming an intermediate layer with a cystic cavity that communicates with the root of the aorta or ventricle. It has low morbidity and high mortality rates. Case presentation Case 1: A 58-year-old male with a history of hypertension and smoking presented to a local hospital due to chest tightness and pain for 4 days. Coronary angiography revealed diffuse lesions from the proximal to the middle segment of the left circumflex branch, with 80% stenosis at its most severe point, and complete occlusion of the proximal segment of the right coronary artery. A stent was implanted in the middle of the right coronary artery. Three months later, the patient was misdiagnosed with an aneurysm of the membranous ventricular septum with defect via echocardiography at the local hospital. After the implantation of a stent in the left circumflex branch, the patient came to our hospital for further diagnosis and treatment. The first ultrasound of our hospital misdiagnosed it as ventricular septal rupture, and a senior ultrasound doctor diagnosed the patient with interventricular septal dissection secondary to myocardial infarction. The patient underwent follow-up echocardiography every 1–2 months for 6 months. The patient remains asymptomatic with stable hemodynamics. The original treatment regimen and follow-up continues. Case 2: A 70-year-old male was admitted to a local hospital due to repeated chest distress for more than 20 years that worsened over several hours. Coronary angiography revealed complete occlusion of the right coronary artery. Cardiogenic shock occurred after percutaneous coronary intervention. The initial several echocardiography of the local hospital and our hospital misdiagnosed it as interventricular septal rupture secondary to myocardial infarction. The later echocardiography diagnosed it as interventricular septal dissection with rupture secondary to myocardial infarction. The patient underwent interventricular septal repair and mitral valvuloplasty after 25 days of medical treatment and died of multiple organ failure on the fourth day after the operation. Conclusions These two cases illustrate a complication of acute myocardial infarction and highlight the importance of echocardiography in its diagnosis. By exploring the etiology, pathogenesis, and key diagnostic points of IVSD, this study aims to provide valuable insights for clinical practice.